Investigation of Small-Scaled Soil Structure Model under Earthquake Loads via Small Shaking Table Tests - Mohammed El Hoseny; Jianxun Ma; Dong Luo; Yanchao Yue (Shock and Vibration)
This paper aims to determine the appropriate scaling coefficient rigorously in the dynamic analysis of structures via small shaking table tests to represent the full real case while considering the soil-structure interaction problem. In addition, we investigate the seismic effects of the superstructure with flexible and fixed bases. To achieve this purpose, seven stories of concrete moment-resisting frames supported on silty clay soil were scaled. According to the shaking table specifications, a small-scaled soil-structure model was executed with a scaled factor of 1 : 50. Consequently, the scale steel skeleton model was built to represent the real superstructure. In addition, the laminar soil container for the soil block was constructed to reduce undesirable boundary effects. Three earthquakes have been applied at the superstructure base as a fixed base and at the bottom of the soil block in the soil structure system as a flexible base. The numerical simulations are implemented for scaled and real models. According to obtained results from experimental and numerical investigations, the numerical model achieved good results with experimental observation. In addition, the small scaling factor of 1 : 50 can represent the seismic response of full construction conditions with acceptable precision. It is observed that the flexible base has overestimated in lateral displacement of the real superstructure compared with a fixed base, in which the maximum amplification percentage at the roof floor level reaches up to 98% under seismic load. Otherwise, the shear force distribution along the height and base shear of the superstructure with a flexible base decreases compared with a fixed base. The maximum reduction percentage is 38% under seismic load. Consequently, the safety and cost of the superstructure are affected.